Reputation strategy and analytics in a hyper-connected world - Foster, Chris (U.S.A Wiley, 2016)
"Reputation management techniques that work amidst the unceasing flow of information Reputation Strategy and Analytics in a Hyper-Connected World is a complete guide to corporate communications and reputation management. Covering a range of scenarios from ideal to catastrophic, this book provides a clear blueprint for preparation, execution, and beyond. The discussion focuses on data-driven, evidence-based strategies for the modern digital economy, providing actionable frameworks, practical roadmaps, and step-by-step blueprints for deploying advance analytics, predictive modeling, and big data techniques to successfully manage communications and reputation. You'll learn how the right tools and people get the job done quickly, effectively, and cost-effectively, and how to identify and acquire the ones you need. Coverage includes the latest technology and cutting-edge applications, bringing you up to speed on what excellence in communications can realistically be. We live in an age of interconnectedness and transparency, and information travels at the speed of light to reach nearly every corner of the globe. This book shows you the key strategies and operational tactics required to respond successfully to financially damaging assaults on your company's reputation. Execute world-class corporate communications Prepare for best- and worst-possible case scenarios Manage organizational reputation in the digital economy Pick the right team and the right tools to get the job done Stories, rumors, lies — there is no safe haven. Big data, cloud, and mobile technologies are fueling a perfect storm of immense proportions, overwhelming the capabilities of organizations and individuals attempting to manage their brands and reputations when hit with damaging information or harmful stories. Reputation Strategy and Analytics in a Hyper-Connected World shows you navigate the never-ending information stream to keep your company out of the undertow"--
"This book provides a clear blueprint for preparing and executing world-class corporate communications, PR, and reputation management strategies across a range of scenarios, from best-case to worst-case"--
Keywords: Corporate image; Communication in management; BUSINESS & ECONOMICS / Business Communication / General